Edukasi Gizi tentang Anemia untuk Siswi SMKS Roudlotun Nasyiin Mojokerto - Ruhana, Amalia; Pratama, Satwika Arya; Sholikhah, Desty Muzarofatus; Wardani, Aulia Putri Srie (DEDICATE: Journal of Community Engagement in Education, 2024)
Anemia is a nutritional problem that occurs in adolescents and is often found in developing countries such as Indonesia. Based on the results of the 2018 Basic Health Research report in Indonesia, the prevalence of anemia in adolescent girls is around 27.2%. Adolescent girls who suffer from anemia are at risk of becoming anemic women of childbearing age and then becoming anemic pregnant women. Based on data from the Mojokerto District Health Service, in 2020 there were 3124 pregnant women affected by anemia. Several studies have found that anemia in adolescent girls is caused by a lack of knowledge and understanding about anemia, for this reason it is necessary to provide nutritional education for adolescent girls in the Mojokerto Regency area. Nutrition education is carried out using videos and booklets regarding anemia. Based on the results of the pretest and posttest given to participants before and after the activity, the results showed that the majority of PKM activity participants (71,43) experienced an increase in knowledge about anemia, the average pretest score was 48.57 and the average posttest score was 61. 14